2023
DOI: 10.1038/s41598-023-37384-7
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-natural experimental study on enterprise innovation driven by urban agglomeration policies in China

Abstract: It is of great significance to carefully evaluate the actual impact of macro-policy formulation on promoting micro-enterprise innovation and implementing innovation-driven strategies. This study utilizes data from Chinese listed companies between 2012 and 2019 and takes the implementation of urban agglomeration policies as a natural experiment. By employing the multi-period differential method, the driving mechanism of urban agglomeration policies on enterprise innovation is investigated. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This can impede peripheral cities' motivation to participate. A longterm solution involves the central government's unified and coordinated promotion of urban agglomerations, coupled with improving local government performance assessment mechanisms to reduce local protectionism 31 . This model, combined with exploring mechanisms for sharing benefits and virtuous competition, can be effective in promoting regional cooperation in urban agglomerations.…”
Section: Discussionmentioning
confidence: 99%
“…This can impede peripheral cities' motivation to participate. A longterm solution involves the central government's unified and coordinated promotion of urban agglomerations, coupled with improving local government performance assessment mechanisms to reduce local protectionism 31 . This model, combined with exploring mechanisms for sharing benefits and virtuous competition, can be effective in promoting regional cooperation in urban agglomerations.…”
Section: Discussionmentioning
confidence: 99%
“…Construction of livable cities needs to rationally avoid the siphoning effect between cities. The results of SDM show that the green development efficiency of the region within the YRD urban agglomeration presents a significant negative spatial spillover effect on urban human settlement resilience in the neighboring regions, suggesting a possible siphoning effect between regions [ 59 ]. From the perspective of the urban development process, core city development will be accompanied by the centralized relocation of resources and industries, which may result in the outflow of resources and economic marginalization of the surrounding cities, and thus not be conducive to enhancing the level of urban human settlement resilience within them [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, Liu et al [9] found that AEs' impact on high-quality development unfolds as a U-shaped relationship, thereby implying that such externalities initially impede, but subsequently enhance, high-quality development. Regarding innovation, studies conducted by Yang et al [10], Yao and Wu [11], and Li and Song [12], using spatial econometric models, underscored that AEs can notably foster innovation development in Chinese cities. In the context of environmental pollution, scholarly opinions diverge.…”
Section: Introductionmentioning
confidence: 99%